Studi Tentang Identitas Jati Diri Bangsa Jepang Dalam Kajian Filosofis - Iriyanto Widisuseno (Diponegoro University, 2019)
(Title: STUDY OF THE JAPANESE NATION'S SELF-IDENTITY IDENTITYIN THE PHILOSOPHY STUDY) This research examines the identity of the Japanese nation through a philosophical approach. Philosophical approach wants to explore the basic values of life that are so fundamental to animating and giving character to the way of thinking and perspective on the meaning of life and life in society and nation. The Japanese nation is known to have a figure of independence, hardworking, resilient and polite, so it is always considered a model of a country that successfully runs modernization based on the values of its cultural traditions. The role of the Japanese state for the progress of the Indonesian economy is very large, especially through services and industry investment programs. The results of the study found Bushido as the basic value of life that animates and gives character to the way of thinking in interpreting the life and life of the Japanese nation. Bushido in its manifestation as the identity of the Japanese nation through eight Bushido virtues which contain moral values: Gi (integrity), Yu (courage), Jin (generous), Jin (generous), Rei (respect and courtesy to others), Makoto - Shin (Honesty and sincerity), Meiyo (maintaining good name and honor), Chugo (loyalty to leaders), Tei (caring). The results of this study can inspire the development of strategies and substance of character education in Indonesia.